Pengembangan Teori Akuntansi Berbasis Filsafat Ilmu - Muntu Abdullah (AKRUAL: JURNAL AKUNTANSI, 2011)
AbstractThe aim of this article is to point out the function of philosophy of science as a foundation to develop accounting theory. Historically, there are some philosophy branches developed. Nowadays, one of the philosophy branches that often used to develop accounting theory is philosophy of science. Philosophy of science is often used by accounting experts to build up accounting theory. The development of accounting theory and accounting thought is overly influenced by the basic assumption that the experts normally use. Just as four paradigms of social reality: Functionalist, Interpretative, Radical Humanist and Structuralist. The classification of these thoughts is based on the research and practice accounting which are in progress. This ism is called contemporary accounting backers. In philosophy of science, a theory is constructed by using a positive preposition and a hypothesis. It starts with an observation and then via induction process, it brings out a positive preposition. Afterwards, a positive preposition and an apriori assumption process a deduction so that bring out hypothesis preposition. The next step is examine the hypothesis in order to produce a theory which can be applied as a foundation to make rules, procedures, methods in carrying out practice accounting.